2016
DOI: 10.1002/chem.201602595
|View full text |Cite
|
Sign up to set email alerts
|

The Unanticipated Dimerization of Ce@C2v(9)‐C82 upon Co‐crystallization with Ni(octaethylporphyrin) and Comparison with Monomeric M@C2v(9)‐C82 (M = La, Sc, and Y)

Abstract: We report that Ce@C (9)-C forms a centrosymmetric dimer when co-crystallized with Ni(OEP) (OEP = octaethylporphyrin dianion). The crystal structure of {Ce@C (9)-C } ⋅2[Ni(OEP)]⋅4 C H shows that a new C-C bond with a bond length of 1.605(5) Å connects the two cages. The high spin density of the singly occupied molecular orbital (SOMO) on the cage and the pyramidalization of the cage are factors that favor dimerization. In contrast, the treatment of Ni(OEP) with M@C (9)-C (M = La, Sc, and Y) results in crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
(140 reference statements)
5
21
0
Order By: Relevance
“…Unexpectedly, subsequent reports demonstrated that a regioselective dimerization can be observed in the crystalline states of Y@ C s (6)‐C 82 (Figure a) and Er@ C s (6)‐C 82 (Figure b) upon co‐crystallization with Ni(OEP) (OEP is the dianion of octaethylporphyrin) in which two fullerene cages are connected by a C−C single bond. Another dimer of pristine EMFs was also observed in the cerium‐containing mono‐EMF co‐crystals (Figure c), [Ce@ C 2 v (9)‐C 82 ] 2 ⋅ 2[Ni(OEP)] . However, no dimerization occurs for M@ C 2 v (9)‐C 82 (M=Y, Er, Sc, La) under the same crystallization conditions .…”
Section: Monometallofullerenesmentioning
confidence: 83%
See 2 more Smart Citations
“…Unexpectedly, subsequent reports demonstrated that a regioselective dimerization can be observed in the crystalline states of Y@ C s (6)‐C 82 (Figure a) and Er@ C s (6)‐C 82 (Figure b) upon co‐crystallization with Ni(OEP) (OEP is the dianion of octaethylporphyrin) in which two fullerene cages are connected by a C−C single bond. Another dimer of pristine EMFs was also observed in the cerium‐containing mono‐EMF co‐crystals (Figure c), [Ce@ C 2 v (9)‐C 82 ] 2 ⋅ 2[Ni(OEP)] . However, no dimerization occurs for M@ C 2 v (9)‐C 82 (M=Y, Er, Sc, La) under the same crystallization conditions .…”
Section: Monometallofullerenesmentioning
confidence: 83%
“…Another dimer of pristine EMFs was also observed in the cerium‐containing mono‐EMF co‐crystals (Figure c), [Ce@ C 2 v (9)‐C 82 ] 2 ⋅ 2[Ni(OEP)] . However, no dimerization occurs for M@ C 2 v (9)‐C 82 (M=Y, Er, Sc, La) under the same crystallization conditions . Density functional theory (DFT) calculations on Y@ C s (6)‐C 82 and Er@ C s (6)‐C 82 reveal that the high spin density caused by the stable displacement of metal atoms in the C s (6)‐C 82 cage should be responsible for the regioselective dimer formation .…”
Section: Monometallofullerenesmentioning
confidence: 91%
See 1 more Smart Citation
“…Our optimized geometry is very similar to the single crystal structure of Th@C 3v (8)‐C 82 , and both of them show an metal position close to the three pentagons of THJ fragment (Scheme ). In the conventional M@C 2v (9)‐C 82 (M = Sc, Y, La, Ce, Eu, Gd, etc), the metals are all perfectly located under a hexagonal ring on the C 2 axis with the C 2v cage symmetry intact. In sharp contrast, Th@C 2v (9)‐C 82 shows an off‐axis metal position with the Th atom situated close to three THJ pentagons, and the molecular symmetry reduces to C s accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the neutral singly bonded (C 59 N) 2 dimer, isoelectronic with the (C 60 − ) 2 dimer, begins to dissociate only above 500 K . Several examples of neutral dimers of paramagnetic monometallofullerenes have been studied in the solid phase, but their thermal stability has not been investigated . In contrast to empty fullerenes, endometallonitridofullerenes experience intrinsic charge transfer from the M 3 N cluster to the fullerene cage, thereby increasing the negative charge on the cage and a large positive charge appears on the scandium atoms.…”
Section: Resultsmentioning
confidence: 99%